Ureteral avulsion as a complication of ureteroscopy - J.M. Alapont; E. Broseta; F. Oliver; J.L. Pontones; F. Boronat; J.F. Jiménez-Cruz (International Brazilian Journal of Urology, 2003)
PURPOSE: Report and review the literature on ureteral avulsion as a rare complication of ureteroscopy. MATERIALS AND METHODS: We analyzed 3 cases of ureteral avulsion in a series of 4,645 ureteroscopic procedures performed from January 1990 to December 2001. We especially report the different managements for this complication. RESULTS: Due to the different extent of the injury, each patient was treated in a particular way, including a patient managed by means of an endourological approach. CONCLUSIONS: When performing ureteroscopy or using Dormia baskets, one should always bear in mind the possibility of serious complications, including ureteral avulsion or perforation. The use of an extremely careful technique of ureteral insertion, the mandatory placement of a safety guidewire, and a working guidewire, all minimize the risk of untoward events.